Al-Islam Dan Kemuhammadiyahan Sebagai Kurikulum Ideologis: Analisis Kritis Das Sollen Dan Das Sein Dalam Pendidikan Tinggi Muhammadiyah - Edo Ferdian; Malik Ashari; Syamsul Arifin; Heri Rifhan Halili (Education Reserach Center, 2025)
This study aims to analyze AIK as an ideological curriculum in Muhammadiyah higher education through the framework of critical analysis of das sollen and das sein. This research uses a qualitative approach with the type of library research, with data sources in the form of official AIK documents, Muhammadiyah higher education curriculum, and relevant scientific literature that is analyzed through content analysis and critical approaches. The results of the study show that at the das solen level, AIK is formulated as an ideological curriculum that integrates theological, ethical, and intellectual dimensions in the mission of da'wah and tajdid of Muhammadiyah. However, at the water level level, the implementation of AIK still tends to be formalized, the dominance of textual and one-way pedagogical approaches, and the weak integration of AIK with the cross-disciplinary academic ecosystem. The gap between normative ideals and implementive realities is influenced by structural factors (pragmatic orientation of higher education, accreditation demands, academic competition) and cultural factors (academic culture that emphasizes technical achievements). This study concludes that strengthening AIK as an ideological curriculum requires systemic transformation that includes the repositioning of AIK as an educational paradigm, strengthening dialogical-reflective pedagogy, and integrating AIK values in institutional policies and campus culture.